Eksplorasi Senyawa Alkaloid Carbazole Murraya microphylla sebagai Antikanker Inhibitor SIRT1 dan CDK9: Studi In Silico - Raihan, Muhammad (Unesa Journal of Chemistry, 2024)
Cancer is currently a major health problem due to its significantly increasing number of deaths and prevalence, including breast cancer and cervical cancer. The development of new drugs is a major effort to overcome the risk of cancer. Natural compounds are the main source of medicinal compounds and are believed to have lower toxicity than synthetic drugs. This study aimed to reveal the anticancer activity of Murraya microphylla carbazole alkaloids as SIRT1 and CDK9 inhibitors in silico. Based on the results of molecular docking simulations, isomahanimbine and mahanimbine compounds were obtained as SIRT1 inhibitors, and girinimbine and koenigine compounds were obtained as CDK9 inhibitors with binding energy values lower than those of control inhibitors, indicating that these compounds have potential as anticancer agents. Prediction of the physicochemical properties, drug-likeness, and pharmacokinetics of the four compounds showed good results and fulfilled the criteria for medicinal compounds. Further research is needed to reveal the potential of these compounds as anticancer drugs.